Application of horizontal series filtration in greywater treatment: a semi-industrial study. Issue 2 (2nd July 2020) - Bahrami, Mehdi; Amiri, Mohammad Javad; Badkubi, Morteza
ABSTRACT: One of the important alternative water sources for non-potable purposes is greywater, but needs to remove contaminants. The aim of this study was to investigate the performance of a horizontal series filter (HSF) consists of sand, zeolite (Z), pumice (P), and granular activated carbon (GAC) to analyse the chemical oxygen demand (COD), biochemical oxygen demand (BOD5 ), total dissolved solids (TDS), turbidity, and pH in greywater samples from Fasa University Student Hostel, Iran. Recycling treatment was performed by passing the greywater through filters. After the last filter, treated greywater was returned into the main tank. The system was run at filtration rate of 2.94 m 3 day −1 . The analysis of the data from the filtration tests showed that GAC is the best adsorbent for removing COD, BOD5, and TDS from greywater, followed by zeolite. Whereas, pumice is more advisable to remove turbidity. However, due to the different mass of adsorbents in the filters, pumice showed a higher adsorption capacity than zeolite. Generally, the triple combination of GAC+Z + P represented the best performance in the reduction of COD, BOD5, TDS, turbidity up to 90.42%, 91.43%, 82.95%, and 90.27%, respectively. Therefore, the studied system can be implemented in public places to greywater treatment and reuse.